Основні етапи заселення гірської місцевості Українських Карпат - Мирослав Дністрянський; Dnyisztrjanszkij Miroszlav; Miroslav Dnistryanskyi („RIK-U” Kft., 2020)
Abstract. Prerequisites and beginnings of mass settlement of the Ukrainian Carpathian mountainous terrain are revealed. The main periods in the process of formation of new settlements in the Ukrainian Carpathian highlands are highlighted. The main factors and ethnic characteristics of each stage of settlement are characterized. The role of different migration movements in these processes is revealed. The conclusion about the decisive role in the development of mountainous areas of the Ukrainian Carpathians resettlement from the foothills is made.
Main stages of the population of the mountain village of the Ukrainian Carpathians
https://kmf.uz.ua/wp-content/uploads/2020/09/final_1_kotet-foldrajzfkonf-2020-07-14.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008119
Keywords: Ukrainian Carpathians; settlement of mountainous areas; formation of settlements; southern colonization of Ukrainian Carpathians